Class Management Based on Non-Discrimination for Children with Special Needs in Inclusive Education Program in Lampung - Sowiyah Sowiyah; Handoko Handoko; Sheren Dwi Oktaria (UIN Fatmawati Sukarno Bengkulu, 2026)
Inclusive education requires non-discriminatory classroom management to support diverse learners, including students with special educational needs. This study investigates the implementation of non-discriminatory classroom management in inclusive primary schools in Lampung Province, Indonesia. A quantitative survey was conducted involving 173 teachers and educational staff. Non-discriminatory classroom management was measured using eight indicators, including behavioral equality, inclusive environment, language use, responsiveness to diversity, student participation, anti-bullying education, accessibility, and human rights education. The findings indicate a high level of implementation, with an overall mean score of 4.46 on a five-point Likert scale. Behavioral equality, student participation, and anti-bullying education emerged as the strongest indicators, while inclusive language use and accessibility showed comparatively lower scores. The novelty of this study lies in its indicator-based, classroom-level assessment of non-discriminatory classroom management, which remains underexplored in inclusive education research, particularly in developing country contexts. The study contributes empirical evidence from Indonesia and provides a practical framework to inform inclusive education policy, teacher professional development, and equitable classroom management practices.